Psychology of gang involvement - Wood, Jane L.; Mallion, Jaimee; Frisby-Osman, Sarah (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Psychology of Gangs expands existing knowledge by applying psychological knowledge to gangs, including how gang members think, their mental and emotional wellbeing, and their perceptions of gang involvement, as well as issues relating to gang prevention and intervention strategies. This book offers readers a clearer understanding of the important role that social psychological processes play in the formation and maintenance of gangs and gang membership. It will enhance readers' understanding of gang members' social cognition, emotional intelligence, wellbeing, and mental health, as well as how these factors potentially promote and sustain individual gang involvement. Readers will discover also how these important psychological characteristics vary according to an individual's commitment to a gang. Organized in three sections, the first focuses on issues relevant to theoretical perspectives of gang involvement. Chapters include detailed examinations of a gang member's experiences, and the implications of these for theoretical development, and considerations of the importance that social psychological issues such as group processes and levels of commitment to gang membership, to understanding and explaining involvement in gangs. The second section centres on issues such as adverse childhood experiences and trauma, and examines their links to male and female gang membership as potential risk factors, and potential outcomes of gang involvement. The section concludes by contemplating how the mental health, traumatic experiences, and involvement in violence compares between gang members and other violent men in adulthood. The final section evaluates current responses to gang membership by evaluating individual and group-based approaches to gang prevention and intervention strategies, and concludes with a theoretical conceptualization of how a strengths-based approach could work to reduce gang involvement. This book will be a useful text for a wide range of readers interested in, or working with, gang members, including academics and students, practitioners, youth workers, clinicians, and criminal justice agents"--
OCLC-licensed vendor bibliographic record.
Keywords: Gangs -- Psychology; Criminal psychology; PSYCHOLOGY / Forensic Psychology; SOCIAL SCIENCE / Criminology